Practices and Perceptions on Contraception Acceptance among Clients Availing Safe Abortion Services in Nepal - Khanal, V; Joshi, C; Neupane, D; Karkee, R (Kathmandu University Medical Journal, 2012)
Background The Government of Nepal has implemented safe abortion policy since 2002. There are 245 approved sites providing safe abortion services to women across the country. Family planning counselling is one of the components of the safe abortion policy, which is important to reduce unwanted pregnancy, maternal morbidity and mortality due to the consequences of unsafe abortion and the service burden. Objectives This study explains the perceptions, practices and factors affecting the use of family planning among abortion clients attending safe abortion services in Nepal. Methods A cross sectional study was carried out on September, 2008 enrolling 58 women who were waiting in the dressing room for safe abortion services in Paropkar Maternity Hospital, Nepal. All women attending hospital clinic for receiving safe abortion services were approached for interview till the targeted number was fulfilled. A convenience sampling was applied to reach the sample size. Results Of the 58 respondents, majority of the respondents were Hindus (83%), residing in Kathmandu district (76%); of the age group 20-29 years (69%); and 98% were married. One fifth (20.68 %) of the respondents had previous history of spontaneous or induced abortion. The main reason for abortion did not want any more babies/complete family (45%). The knowledge of modern contraception was high (98.27%).The knowledge of emergency contraception was low (25.9%). Side effects was the main reason (48%, n=31) for discontinuation of contraceptives. Intention to use some modern family planning methods after the abortion was expressed by 83% clients. The major enabling factor for continued contraceptive use was the absence of side effects. The family planning counselling was acceptable for 91% clients. Conclusion Knowledge, acceptance of counselling service and intention to use family planning measure was high in the study participants. There is need to provide skills on adapting with the adverse effect of family planning measure through continuous education and reinforcement. DOI: http://dx.doi.org/10.3126/kumj.v9i3.6301 Kathmandu Univ Med J 2011;9(3):179-84